POTENSI PENGEMBANGAN PRODUKSI JAGUNG DI KECAMATAN KELAM PERMAI KABUPATEN SINTANG - Sundi, Sundi; Suyatno, Adi; Maswadi, Maswadi (Agros Journal of Agriculture Science, 2024)
This study aims to analyze the potential for increasing corn production in Kelam Permai Subdistrict, Sintang Regency, West Kalimantan Province. The research method used is descriptive quantitative, utilizing secondary data. The data collected were then analyzed using Location Quotient (LQ), Dynamic Location Quotient (DLQ), and Shift-Share. The results indicate that Kelam Permai Subdistrict has great potential to enhance corn production in supporting food self-sufficiency in Sintang Regency, West Kalimantan Province. Despite a decline in corn production from 2019 to 2023, the high and increasing LQ value demonstrates a higher specialization in corn production compared to the provincial average, and the positive PPW value confirms the district's competitiveness and comparative advantage. However, the negative PP value highlights the need for strategic interventions to address growth obstacles such as climatic conditions, pest infestations, and resource allocation, so that the significant potential of Kelam Permai Subdistrict in corn production can be maximized effectively.